Добро и зло в мультипликационной картине Хаяо Миядзаки «Порко Россо» - Стахевич, A. B. (ХНУРЕ, 2019)
The problem of good and evil, their relationship is one of the most important problems of human existence. In this paper, good and evil will be considered on the example of Hayao Miyazaki’s work in the animated film Porco Rosso